The urban pilgrims in Qoyllurit’i and the mimetic miniature game - Stensrud, Astrid B. (2010)
This article is about the pilgrims from Cusco city who participate in the miniature game in the sanctuary of Qoyllurit’i. Starting with a description of the urban socioeconomic context and the Andean ontology, this text intends to explore how we may understand the game, the meaning of the miniatures, and the importance of the pilgrimage in the contemporary urban context. A strong motivation for going to Qoyllurit’i is to empower the desires of life and ensure economic prosperity for the future through reciprocal relations with places and objects. In these relations, values like respect and faith are important. Using the analytical concepts «virtuality» and «mimesis», the article analyzes the game as a form of communication based in an ontology in which there are no distinctions between nature-culture, signifier-signified, and matter-spirit. Furthermore, it shows that indigenous religious practices are cultural and material processes which are constantly recreated in continuous and reciprocal relations between the rural and the urban. The article is based on two years and two months of ethnographic fieldwork (2001-2002, 200-2007, 2008) in a neighborhood in Cusco city and in three pilgrimages to Qoyllurit’i (2002, 2007, 2008).